Evaluation of the registry service for basic sectors in agriculture - Celia M. Reyes; Reneli Ann B. Gloria (Philippine Institute for Development Studies (PIDS), 2017)
There are many and varied government programs that target the agriculture and fisheries sector, especially the poor. For more efficient and streamlined program targeting, the Aquino administration has initiated the creation of the Registry Service for Basic Sectors in Agriculture (RSBSA), a list of farmers, farm workers, and fisherfolk in the 75 provinces of the country excluding the Autonomous Region in Muslim Mindanao and the National Capital Region. This is currently used by the Department of Budget and Management to target beneficiaries of various government agencies implementing agricultural support programs, and as a basis for issuing allocated budgets for these programs. This paper finds that there are legitimate agricultural producers that are excluded from the list, leakages, difficulty of the registry to be linked with other government databases, and unclear operational definition of farmer. But despite its shortcomings, the authors find that the RSBSA is useful as a targeting tool; the list just needs to be validated and regularly updated.
Keywords: 330; Registry Service for Basic Sectors in Agriculture (RSBSA); program beneficiary targeting; Department of Budget and Management; agricultural insurance; agricultural credit